Model Matematika (Nonlinier) Populasi Anjing Rabies dengan Vaksinasi - Fitri, Ahmad; Oka, Tjokorda Bagus; Widana, I Nyoman (Jurnal Matematika; Vol 5 No 1 (2015)DO - 10.24843/JMAT.2015.v05.i01.p52, 2015)
Rabies is a fatal infectious virus that can attack all mammals especially dogs. Infection happens when there is  interaction between healthy dogs and rabies-infected dogs. In Bali, rabies was first found in late 2008. One of the solutions done by government to the problem is by giving vaccine to healtly dogs, so that they are not easily infected by the virus. Thus, a mathematical model is needed to analyze the development of dogs population in Bali. By using analysis of fixed point and stability on the model, the population of rabies-infected dog was affected by not only the percentage of vaccination but also the number of healthy dogs birth. Lastly, a numeric simulation by using Taylor’s seriesorder was conducted to illustrate and to strengthen the result of the analysis.
Keywords: Rabies, Vaccination, Nonlinear Systems of Differential Equations